Influência da avaliação CAPES nos programas de pós-graduação da área de Ciências Humanas na percepção de gestores e docentes: estudo de caso em universidade pública - Cavalcante, Eliane Taboza Barboza (2022)
The growing numbers of Graduate Programs in Brazil has been extremely important for advances not only in scientific research, how for training many professionals across the country. At the Federal University of Ceará (UFC) the increase in master's and doctoral courses has also been observed, especially in the last decade. However, as well as growth, quality is also critical to the maintenance of these programs. In regards, the main reference for graduate programs is the evaluation carried out every four years by the Coordination for the Improvement of Higher Education Personnel (CAPES), which evaluates the programs by classifying them with concepts from 1 to 7. So the main objective of this study is to analyze the influence of CAPES assessment in postgraduate programs in human sciences area in the perception of coordinators and professors. To this approach, it is a quantitative-qualitative research and regarding the objectives, it is classified as a descriptive research. The research data were collected through the evaluation forms of the programs and sending questionnaires to professors and coordinators of six graduate programs in the area of human sciences at UFC. The study was consisted of 55 professors and 6 coordinators. The results obtained showed that the evaluation carried out by Capes is well accepted by professors and coordinators, despite criticisms regarding its competitive and homogenizing character. The research also showed the latest results of this evaluation were the subject of debates between students, professors, program coordinators and higher management, being a reference for planning and carrying out actions in stricto sensu graduate programs.